2019
DOI: 10.1038/s41467-019-09805-7
|View full text |Cite
|
Sign up to set email alerts
|

Liquid marble-derived solid-liquid hybrid superparticles for CO2 capture

Abstract: The design of effective CO 2 capture materials is an ongoing challenge. Here we report a concept to overcome current limitations associated with both liquid and solid CO 2 capture materials by exploiting a solid-liquid hybrid superparticle (SLHSP). The fabrication of SLHSP involves assembly of hydrophobic silica nanoparticles on the liquid marble surface, and co-assembly of hydrophilic silica nanoparticles and tetraethylenepentamine within the interior of the liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 52 publications
1
48
0
Order By: Relevance
“…While still providing very large surface areas due to their inner porosity (emergence), [ 39,40 ] SPs can provide sizes in the large micrometer (to sometimes even millimeter) scale and can thus be directly utilized for gas adsorption processes in common industrially used fixed or fluidized bed reactors. [ 41,42 ] Furthermore, their larger sizes compared to NPs also enable a better incorporation without aggregation into filters and a longer sustainment in those. [ 43 ]…”
Section: Supraparticles For Sustainabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…While still providing very large surface areas due to their inner porosity (emergence), [ 39,40 ] SPs can provide sizes in the large micrometer (to sometimes even millimeter) scale and can thus be directly utilized for gas adsorption processes in common industrially used fixed or fluidized bed reactors. [ 41,42 ] Furthermore, their larger sizes compared to NPs also enable a better incorporation without aggregation into filters and a longer sustainment in those. [ 43 ]…”
Section: Supraparticles For Sustainabilitymentioning
confidence: 99%
“…This system exhibited a very high sorption capacity and rate, as well as long‐term stability with reduced amine loss in fixed bed reactors (Figure 2b2). [ 41 ] Another SP system addresses the pollution of air by electromagnetic waves, which are emitted by electronic devices and harm human health. [ 44 ] Carbon‐coated iron oxide NPs (Fe 3 O 4 @C) assembled into larger entities efficiently absorb these waves due to their supraparticulate structure (Figure 2c).…”
Section: Supraparticles For Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…(d) In addition, although these and true Pickering emulsions may show limited coalescence and Ostwald ripening in the absence of shear, shear can be quite disruptive to Pickering emulsions. Rong et al [15] have also shown that if the fluid regions either side of the interface of a droplet in a shear field can distort even a fraction, this concentrates all the transmitted stress between the adsorbed particles to a very small number of particles, such that can easily exceed the desorption energy. This possibly explains the relatively poor resistance of Pickering emulsions to shear, although this has not been studied widely.…”
Section: Ongoing Fundamental Issuesmentioning
confidence: 99%
“…[23][24][25][26][27] Given the exibility in the choice of solid particles and liquids to fabricate liquid marbles, liquid marbles are emerging as a versatile platform for a wide range of applications in miniature reactors, microuidics, drug transport, gas sensing, and biomedical and genetic analyses. [2][3][4][5][6] As a versatile and cost-effective miniature reactor providing a well-conned microenvironment, [28][29][30][31][32] progress in miniaturized chemical and biological processes using liquid marbles has been reported recently. The miniaturized synthesis of graphene/ Ag nanocomposites was demonstrated using liquid marbles.…”
Section: Introductionmentioning
confidence: 99%